Determination of lead, cadmium, zinc and nickel in edible oil products by stripping voltammetry / Ng Khan Loon - Ng, Khan Loon (2010)
Edible oil products had become an everyday food that been consumed by most of the people either for dressing or for cooking purpose. Metal has become a common contamination to the food product, which it found the way into the edible oil through environment and processing contamination such as crushing, distillation, and hydrogenation. In this Study, the main focuses of metal analysis are only confined to 4 common metals which are the Cadmium, Lead, Zinc and Nickel. These elements are selected in this study due to reason that Cadmium and Lead are commonly known for their contamination from environment and from processing equipment, and it is important to be analyzed due to its health deteriorations to consumer. Nickel was chosen in this analysis for its well known function as a catalyst for hydrogenation process in edible oil and Zinc was known to be a micronutrient however excess concentration maybe impact to human health. From analytical chemistry point of view, Spectroscopic techniques particularly Atomic Absorption Spectroscopy (AAS) and Inductively Couple Plasma Optical Emission Spectroscopy (ICP-OES) are some of the well known techniques used for the analysis of metal, however in this study a second approach by electrochemistry technique is employed to study and quantify the metal concentration, the method used is known as Voltammetry Stripping Technique. The advantages of voltammetry technique in comparison to others is it allows for detection limit of sub part per billion level, non destruction method as well as simultaneous determination of some metals. In this study, standard addition method was used as the calibration technique for the determination of Zinc, Nickel, Lead and Cadmium in the edible oil products.